Differences between black-and-white cows with alternative genotypes of the alpha-lactalbumin gene in milk features - Yanbaev Yulay; Paramonova Maria; Valitov Farit; Ianbaev Ruslan; Miftakhov Ilnur (BIO Web of Conferences)
The article presents the study results of the influence of the alpha-lactalbumin gene various genotypes on milk production and the qualitative composition of milk from black-and-white cows bred in the Republic of Bashkortostan. The predominant number of individuals carrying the LALBAAB genotype was found in the analyzed animals in the number of 276 animals (n=175, 63.4%). It was further established that the best characteristics were possessed by the cows containing the allele A in their genotype for the gene under study. These animals were superior to their peers in all indicators of the qualitative composition of milk and milk productivity. The obtained results indicate that genotypes of the milk protein gene under study having the allele A in their composition, including in the heterozygous state, are potentially desirable.